Impact of Key Marketing Tools on Global Car Market Development - Oleksandr Savych; Tetiana Shkoda (Communications - Scientific letters of the University of Zilina, 2021)
The purpose of the proposed study was to identify the functional patterns of influence of the marketing tools on sales of cars on the global market, to be able to predict sales volumes in the future, taking into account certain marketing tools that the company may use in a particular international market. For the purpose of this research the method of correlationregression analysis is used to construct the corresponding economic and mathematical models of impact on the sales volumes of various instruments of product, price, promotion policy, etc. Using the models offered in the article, the feasibility of introducing certain measures can be determined, when entering new markets in order to increase car sales. Each instrument to which potential buyers are sensitive determines the effect of its use. Considering this effect, budgets can be set up for appropriate action.